EXPLOITATION OF THE ELDERLY IN THE PHENOMENON OF ‘CYBER BEGGING’ ON TIKTOK: A VICTIMOLOGICAL PERSPECTIVE - Amalia, Bunga Rizky; Nuroini, Indi (jfpublisher, 2025)
The emergence of cyber begging on digital platforms such as TikTok has raised serious legal and ethical concerns, particularly when involving vulnerable populations like the elderly. This study examines the phenomenon of elderly individuals participating in live-stream content on TikTok, where they are often depicted in humiliating or infantilizing situations in exchange for virtual gifts. Using a normative legal research method, this paper analyzes whether such practices can be categorized as criminal exploitation under Indonesian law, particularly Law No. 21 of 2007 on the Eradication of Human Trafficking and related statutory instruments. The study adopts a victimological perspective to argue that apparent consent does not negate victimhood when participation is shaped by structural conditions such as poverty, digital illiteracy, or dependency. Furthermore, the principle of legal certainty is employed to highlight the inadequacy of current legal frameworks in addressing emerging forms of digital exploitation. The findings suggest that while cyber begging may appear voluntary, it often reflects deeper patterns of coercion and asymmetrical benefit, warranting clearer legal recognition and protective policies. This research contributes to the discourse on elder justice, digital labor ethics, and the evolution of criminal law in the digital age.